2019
DOI: 10.1177/0162643419836411
|View full text |Cite
|
Sign up to set email alerts
|

Augmented Reality: Teaching Daily Living Skills to Adults With Intellectual Disabilities

Abstract: Independent living is recognized as a marker of adulthood. For individuals with intellectual and developmental disabilities, however, the need for continued support in completing daily living tasks reduces the likelihood of achieving independence in this domain. Barriers to living independently include increased dependence on family and support staff and deficits in functional life skills. In this study, a multiple-baseline across behaviors design was used to examine the efficacy of an augmented reality interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
57
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(63 citation statements)
references
References 33 publications
(45 reference statements)
0
57
0
Order By: Relevance
“…AR offers the potential to support individuals with SEN and enable the development of skills to support daily living (Bridges et al, 2019). The use of AR to develop functional skills may reduce dependence on traditional learning and teaching strategies, allow individualization of educational programs, and enable practice on a daily basis (Yuen, 2011).…”
mentioning
confidence: 99%
“…AR offers the potential to support individuals with SEN and enable the development of skills to support daily living (Bridges et al, 2019). The use of AR to develop functional skills may reduce dependence on traditional learning and teaching strategies, allow individualization of educational programs, and enable practice on a daily basis (Yuen, 2011).…”
mentioning
confidence: 99%
“…This aspect could be very useful for students with any kind of disabilities. People with disabilities that negatively impact their social skills can use virtual reality to practise and improve their social skills (Bridges, Robinson, Stewart, Kwon & Mutua, 2019;Cascales-Martínez, Martínez-Segura, Pérez-López & Contero, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…It has been observed that the single-subject study design structure was largely adopted to change individuals' behaviors. This approach has either single baselines [57][58][59][60][61][62][63][64] or multiple baselines [10,[65][66][67][68][69][70] with the intervention phase for the same group. The single-subject design was implemented to investigate the change in an individual's behaviors within a small group [57].…”
Section: Study Design and Methodologymentioning
confidence: 99%
“…The individuals suffer from different types of disabilities. The disability categories that have been covered by the study, which can be seen in Table 5, include Autism Spectrum Disorder (ASD) [53,54,64,65,72,78,79], Intellectual Disabilities (ID) [10,58,59,70,80], Learning Disabilities (LD) [57,76], Attention Deficit Hyperactivity Disorder (ADHD) [55,75,81], Cognitive Impairments and Disorders (CI) [52,69,82], Physical and Motor Disabilities (PD) [51,60,62], Hearing Impairments (HI) [71], Neurodevelopmental Disorders (ND) and Down Syndrome (DS) [83], Small Animal Phobias (SAP) [61,63,84,85], Short Term Memory (STM) [86,87] and Mental Ability (MA) [88], as shown in Figure 5.…”
Section: Distribution Of Different Disability Categoriesmentioning
confidence: 99%